SAT0288 Male Gender is Associated with Accelerated Radiographic Progression in Axial Damage but not with Progression of Peripheral Damage. (23rd January 2014) - Eder, L.; Thavaneswaran, A.; Chandran, V.; Cook, R.; Gladman, D. D.
Abstract : Background: Gender-related differences have not been thoroughly explored in Psoriatic Arthritis (PsA). Our group recently reported that men suffered from more severe radiographic damage in their peripheral and axial joints in a cross-sectional analysis. Objectives: We aimed to further investigate whether male gender is associated with increased radiographic progression of joint damage compared to females. Methods: A retrospective cohort analysis was performed among patients who have been followed in a large PsA clinic from 1978 to 2012. Patients were followed according to a standard protocol at 6-12 month intervals. Radiographs of the hands, feet and spine were performed at 2 year intervals. Radiographic damage based on 42 joints in the hands and feet was assessed according to a modification of the Steinbrocker method. Radiographic damage to the lumbar and cervical spine was scored using the modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS). For each patient all available radiographic data were included. Patients who initiated treatment with anti TNFα agents were censored. The outcome of interest was the difference in the modified Steinbrocker score and mSASSS compared to the previous assessment. Multivariate regression analysis using Generalized Estimating Equations (GEE) for repeated measures was used to compare progression in radiographic damage across the genders incorporating available information from all time points. Results: 1067 PsA patients were included in the study (females: 43.5%, males: 56.5%). Females had higher duration of psoriasis (16.8±13.3 vs. 14.1±11.5 years, p<0.001) and PsA (7.6±9.3 vs. 6.2±7.3years, p=0.007). At first visit, mSASSS was higher in males (2.4±7.7 vs. 0.03±0.24, p=0.002) however no difference was found in the mean modified Steinbrocker scores across the genders (p=0.24). Gender was not associated with progression in radiographic damage in the peripheral joints in both univariate and multivariate analyses. In a multivariate regression analysis tender joint count (p=0.007) and modified Steinbrocker score at first visit (p=0.0002) predicted progression in modified Steinbrocker score. In contrast, male gender predicted progression in mSASSS (β=0.25, p=0.04) in multivariate analysis, while the use of Non-Steroidal Anti Inflammatory Drugs (NSAIDs) was found to have a protective effect (p<0.0001). Conclusions: Among patients with PsA, men tend to accumulate more radiographic axial damage compared to women. No effect of gender on progression in radiographic joint damage was observed. It is unclear whether these findings are secondary to differences in occupational physical activity, hormonal changes or other factors. Disclosure of Interest: None Declared